In Search of the Mysterious Alzheimer’s Disease - Acosta, Gabriela Beatriz (2012)
This article present the complexity of Alzheimer’s Disease (AD) improves, the biological bases underlying its pathogenesis are gradually being disclosed, and we can expect that new therapeutic targets will emerge. AD is characterized behaviorally by progressive memory loss and cognitive decline and physiologically by the presence of beta-amyloid peptide (Aβ) and Neurofibrillary Tangles (NFT) in the brain. The aim is to prevent or at least slow down the progression towards clinical impairment. The pathological mechanisms implicated the actions of β-amyloid, the accumulation of aggregates, the inflammatory cascade, oxidative neuronal damage, tau protein alterations and the formation of NFT, synaptic failure and neurotransmitter depletion. Several of these events are common to many slowly progressive neurodegenerative disorders. The familial forms of Alzheimer’s, secondary to inherited mutations have provided an insight into the molecular mechanisms implicated in disease pathogenesis. The underlying cause of AD, as well as its treatment, is still under investigation. A number of valuable diagnostic tools have been developed and continue to be improved. Risk factors for AD include age, genetic predisposition, environmental factors, cardiovascular diseases, diabetes and diet.